HUBUNGAN FAKTOR PSIKOSOSIAL DENGAN KEJADIAN DEPRESI PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA SABAI NAN ALUIH SICINCIN PADANG PARIAMAN TAHUN 2016 - Ulfa Suryani (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Currently worldwide the number of elderly is estimated there are 500 million with an average age of 60 years and is expected in 2025 will reach 1.2 billion. Life expectancy is increasing is not always accompanied by good health always.. The purpose of this study was to determine the relationship of psychosocial factors with incidence of depression in the elderly in the elderly social institution Sabai Nan Aluih SicincinPariaman.This research is using the design of Cross Sectional Study with a sample of 86 respondents. Sampling was conducted with a total sampling technique.Were collected a file using a questionnaire. Processed file in a computerized and analyzed with univariate and bivariate analysis. To determine the relationship of two variables tested chi-sqare statistic.In this study was found (38.4%) older adults experiencing severe grief, (43.0%) older adults experiencing severe loneliness, (37.2%) elderly are not good social interaction, (41.9%) older adults in conflict with a friend not good, (37.2%) older adults experiencing grief all the time, (47.7%). There is a relationship of factors of grief, loneliness, social interaction, conflict with friends, and death with the incidence of depression in the elderly in the elderly social institution Sabai Nan Aluih Sicincin Pariaman.Can be concluded that almost half (47.7%) in severely depressed elderly PSTW Sabai Nan Aluih Sicincin Pariaman, there is a relationship between psychosocial factors with incidence of depression.Keywords:Psychosocial factors, elderly,incidence of depression